The effect of self-concealment on post-traumatic stress symptoms in breast cancer patients: The mediating role of experiential avoidance - Fan Xu; Shaoju Xie; Qiao Li; Xiaoli Zhong; Jiquan Zhang (PLoS ONE, 2026)
Background Breast cancer is a major global health issue. It brings death threats or serious physical injuries to patients, and is a traumatic event that can seriously affect their mental health and lead to post-traumatic stress, which can lead to serious physical, psychological, cognitive, and social dysfunction, and even increase the risk of suicide, and impose a heavy burden on patients and their families. Aim To investigate the mediating effect of experiential avoidance between self-concealment and post-traumatic stress symptoms in breast cancer patients. Methods This study used a cross-sectional survey design. From 15/08/2021 to 31/12/2021, breast cancer patients were recruited as study subjects in the oncology department of a tertiary hospital in Deyang City. Data were collected through the following tools: the general information questionnaire, the Impact of Event Scale-Revised, the Self-Concealment Scale, and the Acceptance and Action Questionnaire-Second Edition. Results 257 breast cancer patients eventually completed the study, all females. Descriptive results showed that breast cancer patients had self-concealment scores (24.75 ± 7.34), experiential avoidance scores (18.48 ± 5.44), and post-traumatic stress symptoms scores (32.29 ± 14.14). Pearson correlation analyses showed that self-concealment was positively correlated with experiential avoidance and traumatic stress response (r = 0.343, 0.467, both P < 0.01); experiential avoidance was positively correlated with traumatic stress response (r = 0.534, P < 0.01). Mediation effect analyses showed that the total effect of self-concealment on post-traumatic stress symptoms was 0.453, with a direct effect path coefficient of 0.310, and the mediation effect path coefficient of experiential avoidance between self-concealment and post-traumatic stress symptoms was 0.142 (95% CI: 0.074 to 0.223), accounting for 31.35% of the total effect. Conclusion Experiential avoidance in breast cancer patients mediates the relationship between self-concealment and posttraumatic stress symptoms. and could guide healthcare professionals in developing tailored interventions to improve the mental health of patients.